IMPACTO DOS CUSTOS CATASTRÓFICOS NO TRATAMENTO DE PACIENTES COM TUBERCULOSE EM 5 REGIÕES DO BRASIL - Guidoni, Leticia Molino (2020)
Introduction: The high costs of treating tuberculosis (TB) can be impoverishing for families. Care costs above 20% of the annual pre-illness family income are considered catastrophic. This study aimed to assess the economic impact at the family level of t